2023
DOI: 10.1002/advs.202301985
|View full text |Cite
|
Sign up to set email alerts
|

Red Light‐Triggered Anti‐Angiogenic and Photodynamic Combination Therapy of Age‐Related Macular Degeneration

Shuting Xu,
Kaixuan Cui,
Kaiqi Long
et al.

Abstract: Choroidal neovascularization (CNV) is the key pathological event of wet age‐related macular degeneration (wAMD) leading to irreversible vision loss. Currently, anti‐angiogenic therapy with anti‐vascular endothelial growth factor (VEGF) agents has become the standard treatment for wAMD, while it is still subject to several limitations, including the safety concerns of monthly intravitreal administration and insufficient efficacy for neovascular occlusion. Combined therapy with photodynamic therapy (PDT) and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…Inadequate VEGF signaling underlies vascular insufficiency in aged mice, , subsequently leading to compromised perfusion, reduced tissue oxygenation, impaired mitochondrial activity, and progressive malfunction of metabolically active organs. Increased circulating VEGF levels maintain youth-like vascular homeostasis and attenuate multiple adverse age-related processes and pathological phenotypes. ,, Our findings strongly support this view and suggest that the biomimetic PCBP nanoheterostructure system is a practical and versatile therapeutic strategy. The system synergizes the therapeutic capacities of nanoparticles, as well as small-molecule drugs.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Inadequate VEGF signaling underlies vascular insufficiency in aged mice, , subsequently leading to compromised perfusion, reduced tissue oxygenation, impaired mitochondrial activity, and progressive malfunction of metabolically active organs. Increased circulating VEGF levels maintain youth-like vascular homeostasis and attenuate multiple adverse age-related processes and pathological phenotypes. ,, Our findings strongly support this view and suggest that the biomimetic PCBP nanoheterostructure system is a practical and versatile therapeutic strategy. The system synergizes the therapeutic capacities of nanoparticles, as well as small-molecule drugs.…”
Section: Discussionsupporting
confidence: 78%
“…Increased circulating VEGF levels maintain youth-like vascular homeostasis and attenuate multiple adverse agerelated processes and pathological phenotypes. 1,49,50 Our findings strongly support this view and suggest that the biomimetic PCBP nanoheterostructure system is a practical and versatile therapeutic strategy. The system synergizes the therapeutic capacities of nanoparticles, as well as smallmolecule drugs.…”
Section: Discussionsupporting
confidence: 78%
“…Targeting of the CNV, precise PDT occlusion of neovascular vessels [4] Verteporfin (VER) Photoactivatable nanosystem (Di-DAS-VER NPs) Light triggerd sustained and controlled drug release [230] Table 2 (continued) inducing ferroptosis. Therefore, by sorting the exosomes secreted by ESIONP-induced M1 polarized macrophages, extremely small iron oxide nanoparticles (ESIONPs) incorporated with exosomes (ESIONPs@Exo) can be obtained (Song et al).…”
Section: Aunpsmentioning
confidence: 99%
“…This red light-triggered intraocular drug release NIM delivery system enabled combined anti-angiogenic and PDT treatment of wAMD, showing that this combination treatment greatly alleviated CNV development compared with monotherapies. Moreover, treatment of CNV with Di-DAS-VER NPs showed minimum systemic and ocular toxicities [230]. Although this NIM delivery system for photodynamic therapy targeting retinal neovascular diseases is currently in the early stages of basic research and development, results to date have demonstrated the advantages and immense potential of these photodynamic NIM delivery systems for the treatment of retinal neovascular diseases.…”
Section: Photodynamic Therapymentioning
confidence: 99%